Studi Pustaka Reaksi Obat yang Merugikan pada Terapi Covid-19 - Riri karima; Fetri Lestari; Suwendar (UNISBA Press, 2024)
Abstract. Coronavirus Disease 2019 or Covid-19 is a new disease that can cause respiratory problems and pneumonia. This disease is caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection. Adverse Drug Reaction (ADR) is defined as the body's response to a drug that is detrimental or dangerous and undesirable that occurs at normal doses used in humans. The aim of this literature study is to provide information to the public and researchers on Covid-19 therapy based on literature studies including the types of ADR that occur and the drugs that cause them. The data used in this research is secondary data. Secondary data is data obtained not from direct observation, but the data is obtained from the results of research conducted by previous researchers. The secondary data sources in question are in the form of literature reviews and primary or original scientific reports contained in articles or journals that have been taken from Google Scholar, Science Direct, Pubmed regarding the undesirable effects of Covid-19 drugs. Based on a study of ten articles in 2020- 2023, it is known that ADR occurred from Covid-19 therapy caused by Covid-19 therapy drugs with reactions in the form of hyperbilirubination, hyperkalemia, increased transminase, liver dysfunction, angioedema and urticaria, and a higher increase in serum creatinine. Abstrak. Corona virus Disease 2019 atau Covid-19 adalah penyakit baru yang dapat menyebabkan gangguan pernapasan dan radang paru. Penyakit ini disebabkan oleh infeksi Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Adverse Drug Reaction (ADR) didefinisikan sebagai respon tubuh terhadap obat yang bersifat merugikan atau berbahaya dan tidak diinginkan yang terjadi pada dosis normal yang digunakan pada manusia. tujuan dari studi literatur ini adalah bahan informasi pada masyarakat dan peneliti pada terapi Covid-19 berdasarkan studi literatur mencakup jenis ADR yang terjadi dan obat penyebabnya. Data yang digunakan dalam penelitian ini adalah data sekunder. Data sekunder merupakan data yang diperoleh bukan dari pengamatan langsung, akan tetapi data tersebut diperoleh dari hasil penelitian yang dilakukan oleh peneliti-peneliti terdahulu. Sumber data sekunder yang dimaksud berupa literatur review dan laporan ilmiah primer atau asli yang terdapat di dalam artikel atau jurnal yang sudah diambil dari google scholar, science direct, pubmed berkenaan dengan efek yang tidak diinginkan pada obat Covid-19. Berdasarkan kajian dari sepuluh artikel tahun 2020-2023, diketahui bahwa terjadi ADR dari terapi Covid-19 yang disebabkan oleh obat terapi Covid-19 dengan reaksi berupa Hiperbilirubin, Hiperkalemia, Peningkatan transminase, Disfungsi hati, Angioedema dan urtikaria, dan Peningkatan kreatinin serum lebih tinggi.